2008
DOI: 10.1016/j.heares.2007.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of unilateral hearing loss: Cortical adjustment to unilateral deprivation

Abstract: The effect of unilateral hearing loss on 2-deoxyglucose (2-DG) uptake in the central auditory system was studied in post-natal day 21 gerbils. Three weeks following a unilateral conductive hearing loss (CHL) or cochlear ablation (CA), animals were injected with 2-DG and exposed to an alternating auditory stimulus (1 and 2 kHz tones). Uptake of 2-DG was measured in the inferior colliculus (IC), medial geniculate (MG), and auditory cortex (fields AI and AAF) of both sides of the brain in experimental animals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 87 publications
3
29
0
1
Order By: Relevance
“…However, there are deprivation studies (involving transient conductive hearing loss) in animals that have shown effects that are consistent with the ABR findings in the present study (Hutson et al, 2008; In humans, tinnitus has been associated with a reduced wave I amplitude but a normal (Schaette and McAlpine, 2011) or enhanced (Gu et al, 2012) wave V amplitude. These results are consistent with increased neural gain between the auditory nerve and central nuclei.…”
Section: Auditory Brainstem Responsesupporting
confidence: 88%
“…However, there are deprivation studies (involving transient conductive hearing loss) in animals that have shown effects that are consistent with the ABR findings in the present study (Hutson et al, 2008; In humans, tinnitus has been associated with a reduced wave I amplitude but a normal (Schaette and McAlpine, 2011) or enhanced (Gu et al, 2012) wave V amplitude. These results are consistent with increased neural gain between the auditory nerve and central nuclei.…”
Section: Auditory Brainstem Responsesupporting
confidence: 88%
“…However, these changes were not observed in the auditory cortex, since each side of the cortex receives sensory inputs from both ears (Hutson et al, 2008). Previously it was shown that epileptic activity increases expression of NGF (Gall and Isackson, 1989; Zafra et al, 1990; Ernfors et al, 1991) and IL1β (Eriksson et al, 2000; Ravizza et al, 2006) and whisker stimulation increases NGF mRNA levels (Schwarting et al, 1994) and the number of TNF-IR cells in the Sctx (Churchill et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetric moderate hearing loss (e.g. by simply plugging one ear) similarly, but less extensively, reorganises the central representation of auditory space and binaural interactions [King et al, 2001;Vale and Sanes, 2002;Vale et al, 2004;Popescu and Polley, 2010;King et al, 2011;Polley et al, 2013], although some differences between moderate and profound hearing loss mechanisms exist [Hutson et al, 2008]. Residual spatial localisation abilities in asymmetric hearing are secured by increasing reliance on monaural (spectral) cues [Slattery and Middlebrooks, 1994;.…”
Section: Aural Reorganisationsmentioning
confidence: 99%
“…Residual spatial localisation abilities in asymmetric hearing are secured by increasing reliance on monaural (spectral) cues [Slattery and Middlebrooks, 1994;. Changes in inhibitory-excitatory balance are involved in these processes [Mossop et al, 2000;Vale and Sanes, 2002;Vale et al, 2004;Hutson et al, 2008].…”
Section: Aural Reorganisationsmentioning
confidence: 99%